2017
DOI: 10.1016/j.neuroimage.2017.07.046
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional, empirical and modeled connectivity in the cerebral cortex of the rat

Abstract: Connectomics data from animal models provide an invaluable opportunity to reveal the complex interplay between structure and function in the mammalian brain. In this work, we investigate the relationship between structural and functional connectivity in the rat brain cortex using a directed anatomical network generated from a carefully curated meta-analysis of published tracing data, along with resting-state functional MRI data obtained from a group of 14 anesthetized Wistar rats. We found a high correspondenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 102 publications
1
38
0
Order By: Relevance
“…Mouse Connectivity Atlas to study structure-function relations at the group level using voltage-sensitive dyes (35) and FC (6,22,36). In addition, a recent work in rats (37) used TVB to simulate FC based on SC and found strong correlation at the group level. A similar finding has been reported in humans (38).…”
Section: Discussionmentioning
confidence: 99%
“…Mouse Connectivity Atlas to study structure-function relations at the group level using voltage-sensitive dyes (35) and FC (6,22,36). In addition, a recent work in rats (37) used TVB to simulate FC based on SC and found strong correlation at the group level. A similar finding has been reported in humans (38).…”
Section: Discussionmentioning
confidence: 99%
“…However, we did not find a correlation between functional connectivity and meso-scale neuronal tracer-based structural connectivity strength. One previous study investigated this relationship at the meso-scale in rats and reported a positive structure-function correlation (r=0.48) (Díaz-Parra et al 2017). However, this study did not include essential interhemispheric connections.…”
Section: Distinct Global Structure-function Relationships Across Diffmentioning
confidence: 99%
“…The simulated data was fitted to determine clinical epilepsy propagation zones. TVB was also used to simulate rat brains (35) and macaque brains (36). With an evolutionary optimization algorithm and the Generic 2D oscillator the simulated FC was tuned to fit its empirical counterpart.…”
mentioning
confidence: 99%